Small business - Ryan, J. D. (Thomson South-Western, 2006)
This book is a guide to small business enterprise, helping the student to identify opportunities, needs and target customers. The practical, step-by-step nature of this text makes it indispensable. The goal of the text is to assist the reader in preparing a business plan that will set the course for their future small business endeavors